Association of cardiometabolic index and new-onset stroke in middle-aged and elderly Chinese: a national prospective cohort study - Yibo Yang; ZhenKun Xiao; Jing Teng; Hailong Zhong; Yonghong Duan; Min Zhou; Bing Wang; Aihua Liu (BMC Neurology)
Abstract Background and aims The Cardiometabolic Index (CMI), a novel metabolic marker, has been associated with various metabolic diseases in previous studies. However, its relationship with stroke risk remains underexplored. This study investigates the potential correlation between CMI and stroke risk among Chinese adults aged 45 and older. Methods In the China Health and Retirement Longitudinal Study (CHARLS), participants were categorized into four groups based on CMI quartiles. The primary outcome was the incidence of new strokes during the follow-up period. A Cox proportional hazards model was used to analyze the relationship between CMI and stroke risk among the elderly. Kaplan–Meier survival analysis compared incidence rates across CMI levels, and restricted cubic splines (RCS) assessed potential non-linear relationships between CMI and stroke. Subgroup analyses verified the robustness of these findings. Results The study included 6620 patients (45% male), with 417 new stroke cases reported over an average follow-up of seven years. Multivariate analysis indicated a significant association between increased CMI and higher stroke risk [HR, 1.132 (1.021–1.273), P = 0.003]. The RCS model revealed a nonlinear increase in stroke risk with rising CMI levels (P for nonlinearity = 0.006). No significant interactions were detected between CMI and the selected subgroups (all P values for interaction > 0.05). Conclusion CMI significantly correlates with stroke risk in the elderly Chinese population, suggesting its potential utility in early risk stratification.